Mexican Quality of Work Life Scale in healthcare personnel: development and validation - Pérez-Ortíz, Alejandro; Antonio-Cruz, Aldo; Neri-Flores, Verónica; Pineda-Flores, Claudia; Romero-Hernández, Astrid X.; Ortega-Luyando, Mayaro; Gutiérrez-Velilla, Ester (Anales de Psicología / Annals of Psychology, 2024)
There is little evidence of measurement scales with appropriate psychometric properties regard Quality of Work-Life in health personnel, so the objective was to develop and examine psychometric properties of Mexican Quality of Work Life Scale (MQWLS). An instrumental, cross-sectional study was conducted. Phase 1) development of the scale and content validity; Phase 2) validation with two different samples [n = 293] and [n = 300] through an online questionnaire. Content validity was obtained for 60 items (Aiken’s V > .90); exploratory and confirmatory factor analyzes yielded a six-dimension structure; the fit indexes from the final scale with 24 items were acceptable (χ2[257] = 540.277; CMIN/DF = 2.102; NFI = .914; CFI = .953; GFI = .877, AGFI = .845; SRMR = .047; RMSEA = .061 [.054-.069] p < .001), with good reliability indices (α = .949, ω = .982). MQWLS proved internal consistency reliability, several evidences of validity and acceptable configurational and metric invariance with a model that confirms the existence of six dimensions that explain the construct through 24 items.